Comparative study between three approaches of ultrasound guided quadratus lumborum block for post-operative analgesia in total hip replacement with spinal anaesthesia - Abdel Wahab A. S.S. Mohammed; Tamer M.A Ewieda; Wael M. Mossa; Abdelfattah M. Abdelfattah; Mohammed H. Alqassas; Ayman S. Abdelaziz Elsaily (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Early postoperative ambulation and reduction of hospital stay necessitate efficient postoperative analgesia. Quadrates Lumborum Block (QLB) has been described to provide adequate postoperative analgesia after abdominal surgery.Objective: compare between different approaches of ultrasound guided quadratus lumborum block for post-operative analgesia in total hip replacement with spinal anaesthesia.Patients and Methods: This study was conducted in Orthopedic surgery operating unit in Al-Azhar University Hospitals (Al-Hussein and Sayed Galal), and approved by the ethics committee from the Department of Anesthesia of Faculty of Medicine, Al-Azhar University. Patients gave written informed consents. A total of 80 patients undergoing total hip replacement with spinal anesthesia were enrolled in our study. Eligible patients were randomly classified into four groups; 20 patients had received lateral QLB (QLB-1), 20 patients had received posterior QLB (QLB-2), 20 patients had received transmuscular QLB (QLB-3). QL blocks were done using 20 ml of Bupivacaine 0.25 %. The remaining 20 patients had received spinal anaesthesia only (SAB) that served as control group.Results: The time of requirement of first analgesia significantly prolonged in QLB-3 compared to QLB-1, QLB-2 and SAB control and prolonged in QLB-1 and QLB-2 than SAB control with insignificant differences between QLB1 and QLB-2. The total doses of rescue morphine were significantly lower in QLB-3 compared to QLB-1, QLB-2 and SAB control, and lower in QLB-1 and QLB-2 than SAB control with insignificant differences between QLB1 and QLB-2. VAS was significantly different among the four groups at 2, 12 and 24 hours (P